PENERAPAN E-GOVERNMENT DI BADAN PENELITIAN DAN PENGEMBANGAN DAERAH KABUPATEN PANGKAJENNE DAN KEPULAUAN (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
This study purposed to find out the implementation of e-government in the Regional Research and Development Agency of Pangkep Regency. This study used qualitative descriptive method. The number of informants in this study were 3 people. The data collection techniques used  interviews, observations, and documents related to the research. The results of this study showed that the implementation of e-government in the Regional Research and Development Agency of Pangkep Regency was quite good. This was evidenced by the indicators of measuring aspects in realizing e-government, namely software, hardware, human resources, data and information, organizational structure, communication, and attitude of implementers. Whereas in realizing the implementation of e-government at the Regional Research and Development Agency of Pangkep Regency, there were obstacles which result in application-based services that could no longer be run and used temporarily by the community. One of the internal factors was the hosting on the application had expired because there was no update and payment for the extension of application usage. Another external factor was the socialization stage which was still not optimal in delivering information about the presence of the Pangkep R&D application.Keywords: E-Government, R&D Applications